Non-linear association between life’s essential 8 score and depression in middle-aged and older adults with chronic obstructive pulmonary disease - Yushan Shi; Di Huang; Linlin Qu; Qingyin Liu; Zhanjun Qiu; Xianhai Chen (PLoS ONE, 2025)
Objective Relatively few studies have investigated the link between the Life’s Essential 8 (LE8) score and depression among individuals with Chronic Obstructive Pulmonary Disease (COPD). Our objective was to explore the potential association between the LE8 score and the presence of depression in adults aged ≥40 years who diagnosed with COPD. Methods Data from the National Health and Nutrition Examination Survey (NHANES) spanning 2005–2018 was used in this study. Weighted logistic regressions, restricted cubic splines (RCS) were utilized to investigate the correlation between LE8 score and depression. Using a two-piecewise logistic regression model to identify potential threshold effects. Subgroups and sensitivity analyses were conducted to test the robust of the association. Results The study encompassed a total of 1,110 subjects diagnosed with COPD. In fully adjusted statistical model, an increment of 10 points in the LE8 score was correlated with a reduced likelihood of depression (OR: 0.68, 95% CI: 0.58–0.78). Similar trends in the associations of health behavior score (OR = 0.75, 95% CI: 0.67–0.84) with depression was also identified. The threshold for the LE8 score was pinpointed at 50.0; surpassing this value, the probability of depression decreased by 8.0% for each additional point in the LE8 score (OR, 0.92; 95% CI: 0.88–0.95; P < 0.001). Furthermore, higher LE8 metric scores of physical activity, nicotine exposure and sleep health were associated with a lower prevalence of depression. The results of subgroup and sensitivity analyses were found to be consistent with the principal analysis. Conclusions There is a non-linear relationship between LE8 score and depression, with an inflection point of roughly 50.0. Adhering to a higher LE8 score (≥50.0) was correlated with lower odds of depression among COPD adults aged ≥ 40years.